2021
DOI: 10.1088/1361-6382/ac213b
|View full text |Cite
|
Sign up to set email alerts
|

Shadows of Lorentzian traversable wormholes

Abstract: The prospect of identifying wormholes by investigating the shadows of wormholes constitute a foremost source of insight into the evolution of compact objects and it is one of the essential problems in contemporary astrophysics. The nature of the compact objects (wormholes) plays a crucial role on shadow effect, which actually arises during the strong gravitational lensing. Current Event Horizon Telescope observations have inspired scientists to study and to construct the shadow images of the wormholes. In this… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 87 publications
0
11
1
Order By: Relevance
“…On the other hand, theoretical investigations of shadow images of compact objects are quite fascinating. This applies not only to black holes in General Relativity [36][37][38][39][40][41][42][43][44][45] and in alternative gravities [46][47][48][49][50][51][52][53][54][55][56], but also to exotic compact objects like wormholes [57][58][59][60][61][62][63][64][65][66][67], naked singlarities [68][69][70][71][72][73][74][75][76][77][78] or boson stars [79,80]. Previous studies have shown that some of these exotic compact objects can mimic black holes with respect to their shadow images if their light ring properties are similar.…”
Section: Jcap05(2024)007mentioning
confidence: 99%
“…On the other hand, theoretical investigations of shadow images of compact objects are quite fascinating. This applies not only to black holes in General Relativity [36][37][38][39][40][41][42][43][44][45] and in alternative gravities [46][47][48][49][50][51][52][53][54][55][56], but also to exotic compact objects like wormholes [57][58][59][60][61][62][63][64][65][66][67], naked singlarities [68][69][70][71][72][73][74][75][76][77][78] or boson stars [79,80]. Previous studies have shown that some of these exotic compact objects can mimic black holes with respect to their shadow images if their light ring properties are similar.…”
Section: Jcap05(2024)007mentioning
confidence: 99%
“…Karakasis et al discussed the wormhole geometries by introducing a phantom scalar field in the gravitational action of f (R) gravity; as a result, it becomes ghost-free and avoids the tachyonic instability [66]. Farook et al studied shadows of a particular class of rotating wormhole, and they compose the null geodesics and study the effects of the parameters on the photon orbit [67]. Kuhfitting addressed two fundamental issues concerning Morris-Throne wormholes in the five-dimensional spacetime, such as the origin of exotic matter and frequently inexplicable enormous radial tension at the throat [68].…”
Section: Introductionmentioning
confidence: 99%
“…This could help us constraining the parameter of these spacetimes (see e.g. [2,14,[23][24][25][26][27][28][29][30][31][32][33]). In this regard, while the notion of black hole event horizons continues to attract much of the attention, horizonless compact objects which mimic black holes are also fast gaining popularity in the literature (see [34] and references therein).…”
Section: Introductionmentioning
confidence: 99%